High‐Valence Co Stabilized by In‐Situ Growth of ZIF‐67 on NiCo‐LDH for Enhanced Performance in Oxygen Evolution Reaction - Huang, Yan‐Kai; Li, Tong; Feng, Han; Lv, Luo‐Tian; Tang, Tong‐Xin; Lin, Zhan; Ye, Kai‐Hang; Wang, Yong‐Qing (Small (Weinheim an der Bergstrasse, Germany), 2025)
The application of metal–organic frameworks (MOFs) in the electro‐catalysis of heterogeneous structures is limited by the problems of low electrical conductivity and poor mechanical strength due to the complex synthesis process, although their high specific surface area and controllable structure. In this study, a method involving metal precipitation and ligand reaction is used during the electrochemical corrosion of hydroxides/oxy‐hydroxides to obtain ZIF‐67 in situ. The in situ growth technology not only effectively addresses the bonding strength and material conductivity challenges in the heterostructure between MOFs and the substrate but also enhances the catalyst's surface area and activity. Additionally, the exposure and protection of Co4+ by ZIF‐67 contribute to the electrocatalyst's performance, demonstrating a low overpotential (η100) of 293 mV, a Tafel slope of 25.8 mV dec−1, and a charge transfer resistance of 3.9 Ω, with long‐term robustness proven in continuous stability test exceeding 75 000 s under the superhigh current density of 500 mA cm−2. This work on binder‐free in situ growth of MOFs not only provides relevant theoretical insights and experimental experience for cost‐effective and controllable production of MOF‐based catalysts but also offers ideas for the development of future electrocatalysts by exploring the exposure and protection of active site using MOFs materials. A multi‐architecture oxygen evolution reaction (OER) catalyst is designed. NiCo‐layered double hydroxide (NiCo‐LDH) and zeolitic imidazolate frameworks‐67 (ZIF‐67) are grown on the surface of nickel foam by alternating cathodic and anodic electrodeposition, so as to realize the in situ growth of metal–organic framework without binder and to mildly product the low‐cost controllable MOF‐based catalysts.